2003
DOI: 10.1074/jbc.m301663200
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Micelles and Vesicles Induce Tau Fibrillization in Vitro

Abstract: Alzheimer's disease is defined in part by the intraneuronal accumulation of filaments comprised of the microtubule-associated protein tau. In vitro, fibrillization of recombinant tau can be induced by treatment with various agents, including phosphotransferases, polyanionic compounds, and fatty acids. Here we characterize the structural features required for the fatty acid class of tau fibrillization inducer using recombinant fulllength tau protein, arachidonic acid, and a series of straight chain anionic, cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
257
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(273 citation statements)
references
References 57 publications
16
257
0
Order By: Relevance
“…These studies suggest that FAs play a pivotal role as nucleates in the self-assembly of misfolded proteins. Although the precise mechanism of how lipid molecules accelerate protein aggregation has not been elucidated, it has been proposed that lipid-bound proteins change their conformation or anionic surfaces, presenting as micelles or vesicles, which can serve to nucleate aggregate formation (18,34,35). We confirmed that apo-SOD1s or heattreated holo-SOD1 mutants were bound to oleic acid (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…These studies suggest that FAs play a pivotal role as nucleates in the self-assembly of misfolded proteins. Although the precise mechanism of how lipid molecules accelerate protein aggregation has not been elucidated, it has been proposed that lipid-bound proteins change their conformation or anionic surfaces, presenting as micelles or vesicles, which can serve to nucleate aggregate formation (18,34,35). We confirmed that apo-SOD1s or heattreated holo-SOD1 mutants were bound to oleic acid (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with earlier observations (47) the CMC for arachidonic acid in assembly buffer alone was measured as 236 Ϯ 12 M, which was well above the concentration required for acceleration of ␣-synuclein fibrillization. When CMC was measured in assembly buffer complete with ␣-synuclein at 15 M, however, the CMC decreased to 10.3 Ϯ 4.8 M. This magnitude of CMC depression is similar to that induced by tau protein (48). These data show that fatty acids such as arachidonic acid aggregate to form micelles at much lower concentrations in the presence of ␣-synuclein than in its absence.…”
Section: Efficient Induction Of ␣-Synucleinmentioning
confidence: 49%
“…Depression of the CMC for anionic detergents is regularly observed in the presence of cationic electrolytes (66) including proteins such as tau (48). But whereas tau protein contains a net positive charge at assay pH, ␣-synuclein is negatively charged.…”
Section: Discussionmentioning
confidence: 99%
“…These inducers, which include anionic surfactant micelles, promote heterogeneous nucleation (i.e., nucleation owing to the presence of foreign particles) on their surfaces from which tau filaments then extend in an elongation reaction [5][6][7]. Tau fibrillization antagonists identified by in *Corresponding Author: Jeff Kuret, Ph.D., Center for Molecular Neurobiology, 1060 Carmack Rd., Columbus, OH 43210, Fax: 614-292-5379, Email address: kuret.3@osu.edu (J. Kuret).…”
Section: Introductionmentioning
confidence: 99%